Infuence of low-frequency quasar 3C 273 radio spectrum on X-ray emission of its kiloparsec jet - Mykhailova, M.S.; Kontorovich, V.M. (Advances in Astronomy and Space Physics, 2011)
In this paper the X-ray emission spectrum from the nearest to the quasar 3C 273 inner jet knot A was investigated by the kinetic equation method. It is shown that the inverse Compton scattering of the quasar radio emission is responsible for the X-ray emission of the knot. Under certain conditions it is possible to determine the position of the low-frequency break in the spectrum of the quasar using the X-ray radiation of its jet.